Quantifying sociodemographic and income disparities in medical therapy and lifestyle among symptomatic patients with suspected coronary artery disease: a cross-sectional study in North America. Issue 9 (29th September 2017) - Ladapo, Joseph A; Coles, Adrian; Dolor, Rowena J; Mark, Daniel B; Cooper, Lawton; Lee, Kerry L; Goldberg, Jonathan; Shapiro, Michael D; Hoffmann, Udo; Douglas, Pamela S
Abstract : Objectives: To evaluate potential gaps in preventive medical therapy and healthy lifestyle practices among symptomatic patients with suspected coronary artery disease (CAD) seeing primary care physicians and cardiologists and how gaps vary by sociodemographic characteristics and baseline cardiovascular risk. Design: Cross-sectional study assessing potential preventive gaps. Participants: 10 003 symptomatic outpatients evaluated by primary care physicians, cardiologists or other specialists for suspected CAD. Setting: PROspective Multicenter Imaging Study for Evaluation of Chest Painfrom 2010 to 2014. Measures: Primary measures were absence of an antihypertensive, statin or angiotensin-converting enzyme inhibitor/angiotensin receptor blocker for renal protection in patients with hypertension, dyslipidaemia or diabetes, respectively, and being sedentary, smoking or being obese. Results: Preventive treatment gaps affected 14% of patients with hypertension, 36% of patients with dyslipidaemia and 32% of patients with diabetes. Overall, 49% of patients were sedentary, 18% currently smoked and 48% were obese. Women were significantly more likely to not take a statin for dyslipidaemia and to be sedentary. Patients with lower socioeconomic status were also significantly more likely to not take a statin. Compared with Whites, Blacks were significantly more likely to be obese, while Asians were less likely to smoke or be obese. High-risk patients sometimes experienced larger preventive care gaps than low-risk patients. For patients with dyslipidaemia, the presence of a treatment gap was associated with a higher risk of an adverse event (HR 1.35, 95% CI 1.02 to 1.82). Conclusions: Among contemporary, symptomatic patients with suspected CAD, significant gaps exist in preventive care and lifestyle practices, and high-risk patients sometimes had larger gaps. Differences by sex, age, race/ethnicity, socioeconomic status and geography are modest but contribute to disparities and have implications for improving opulation health. For patients with dyslipidaemia, the presence of a treatment gap was associated with a higher risk of an adverse event. Clinical trial registration: Clinical Trials.gov identifier NCT01174550 .